Design of Polarization-Independent Reflective Metalens in the Ultraviolet–Visible Wavelength Region - Guo, Huifang (Nanomaterials (Basel), 2021)
Flat lens or metalens, as one of the most important application branches of metasurfaces, has recently been attracting significant research interest. Various reflective and transmissive metalenses have been demonstrated in the terathertz, infrared and visible wavelength range. However, metalens operating in the ultraviolet (UV) wavelength range is rare. Moreover, the development of reflective UV metalens, the important counterpart of transmissive ones, falls far behind. In this work, with thorough investigation of material properties, we propose a reflective metalens based on silicon dioxide (SiO(2)) and aluminum (Al) that operates in the vacuum ultraviolet (VUV) to visible wavelength region. Four reflective metalenses were designed and optimized for wavelengths of 193, 441, 532 and 633 nm, and prominent focusing capability was observed, especially for the VUV wavelength of 193 nm. Dispersion characteristics of the metalenses were also studied within ±50 nm of the design wavelength, and negative dispersion was found for all cases. In addition, the SiO(2) + Al platform can be, in principle, extended to the mid-infrared (IR) wavelength range. The reflective VUV metalens proposed in this work is expected to propel miniaturization and integration of UV optics.